Microbiology : an introduction - Tortora, Gerard J.; Case, Christine L., 1948-; Bair, Warner B.; Weber, Derek; Funke, Berdell R. (Harlow, United Kingdom : Pearson, 2025)
"Since the publication of the first edition nearly 30 years ago, well over 1 million students have used Microbiology: An Introduction at colleges and universities around the world, making it the leading microbiology textbook for non-majors. The fourteenth edition continues to be a comprehensive beginning text, assuming no previous study of biology or chemistry. The text is appropriate for students in a wide variety of programs, including the allied health sciences, biological sciences, environmental science, animal science, forestry, agriculture, nutrition science, and the liberal arts"--
Includes index.
Keywords: Microbiological Phenomena; Microbiology